(untitled) (Academia Science Repository, 2023)
The article deals with the issue of achieving gender equality, ensuring the rights, freedoms and legitimate interests of women, strengthening their role in the life of society and the state, which is one of the priorities of the new state policy of Uzbekistan. The basis of this topic is the strategy of actions of the Republic of Uzbekistan.